2023
DOI: 10.3389/fbioe.2023.1257591
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing accuracy in brain stroke detection: Multi-layer perceptron with Adadelta, RMSProp and AdaMax optimizers

Mudita Uppal,
Deepali Gupta,
Sapna Juneja
et al.

Abstract: The human brain is an extremely intricate and fascinating organ that is made up of the cerebrum, cerebellum, and brainstem and is protected by the skull. Brain stroke is recognized as a potentially fatal condition brought on by an unfavorable obstruction in the arteries supplying the brain. The severity of brain stroke may be reduced or controlled with its early prognosis to lessen the mortality rate and lead to good health. This paper proposed a technique to predict brain strokes with high accuracy. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Research studies have shown the use of deep learning models, such as convolutional neural networks (CNN) and multi-layer perceptron's, to assist in the early diagnosis of stroke and improve accuracy in stroke detection. These models are trained using medical imaging data to classify and detect strokes [11], [12]. There are also innovative approaches, such as using skeleton data from neurological examination videos for deep-learning-based stroke screening [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research studies have shown the use of deep learning models, such as convolutional neural networks (CNN) and multi-layer perceptron's, to assist in the early diagnosis of stroke and improve accuracy in stroke detection. These models are trained using medical imaging data to classify and detect strokes [11], [12]. There are also innovative approaches, such as using skeleton data from neurological examination videos for deep-learning-based stroke screening [13].…”
Section: Literature Reviewmentioning
confidence: 99%